KUALITAS PERAIRAN MUARA SUNGAI SIAK DITINJAU DARI SIFAT FISIK-KIMIA DAN MAKROZOOBENTOS - Nur El Fajri; Adnan Kasry (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
This research was conducted on August to October 2011 at Estuary of Siakriver, Riau province. Aimed of this research was measured of water quality. Onphysically of water qulity showed that have high TSS and have low of waterproductivity. Organic substrat still support to macrozoobenthos to live.Kata Kunci : Sungai Siak, Fisik, Kimia, makrozoobentos